Anti-dentine Salivary SIgA in young adults with a history of dental trauma in deciduous teeth - Gabriela Fleury SEIXAS; Cássia Cilene Dezan GARBELINI; Kelly Limi AIDA; Ana Paula CHEIRUBIM; Emerson José VENÂNCIO; Solange de Paula RAMOS (Sociedade Brasileira de Pesquisa Odontológica, 2015)
Anti-dentin autoantibodies are associated with inflammatory root resorption in permanent teeth and are modulated by dental trauma and orthodontic force. However, it is not known whether deciduous tooth trauma can stimulate the development of a humoral immune response against dentin. The aim of this study was to evaluate the levels of salivary SIgA reactivity against human dentin extract in young adults with a history of trauma in the primary dentition. A sample of 78 patients, aged 18 to 25, who had completed an early childhood (0 to 5 years old) caries prevention program years earlier at the Universidade Estadual de LondrinaPediatric Clinic, underwent radiographic examination and salivary sampling. Anti-dentin SIgA levels were analyzed by immunoenzymatic assay and Western blotting. Although dental trauma to deciduous teeth had occurred in 34 (43.6%) of the patients, no differences in SIgA levels were detected between individuals who had experienced trauma and those who had not (p > 0.05). Multivariate regression analysis showed no association between dental trauma and SIgA levels (p > 0.05). Patients with a history of deciduous trauma presented low levels of anti-dentin antibodies, associated with orthodontic root resorption (p < 0.05). Western blot analysis showed that salivary antibodies recognized a single band of approximately 45 kDa in dentin extract. We concluded that salivary SIgA recognizes a specific component of the dentin matrix and that anti-dentin antibodies were not triggered by trauma to primary teeth. However, trauma to deciduous teeth may down-modulate SIgA in response to orthodontic root response.